A educação de jovens e adultos na perspectiva da inclusão: o olhar das professoras - Souza, Sandra Cristina Morais de (2013)
The objective of this research is analyze, by the view of the professors, the process of the inclusion of the younger and adults with physical and psychology disability at the EJA( Young and Adults Education), at some municipal public schools of João Pessoa city, Paraiba State Capital, Brazil. At the Historical context of the Brazilian Education, the EJA has always represented a place of battles against the social exclusion. Starting on this point, this study shows a investigation about the other population that also is submitted a certain exclusion, the people who has some kind of disability, that have been also included in the statistics of the exclusion. This study is based in the documents available by the Education e Cultural Secretary of João Pessoa City, in which was possible an analyze of the students chart with disability at the EJA in the 2011 year. As a general guiding, this work has intended to explain these themes starting with the contribution of the Theoretical Cultural Researches, with focus in questions like: What the principal kinds of disabilities that existing in the EJA Schools modality? What the principal difficulties faced by the teachers who works with a student that shows some kind of disability? What the level of evasion and permanency of the young and adults with these disabilities in the EJA s modality? What the profile of the teachers who works at the EJA and which is theirs view about social inclusion? Based in these guiding questions, eight teachers were interviewed and observed in practice, where, at the EJA, they work with disability students. They have been studied in five different institution of public education in the city. The results obtained indicated the existence of a divergence, discordance between the inclusion policies and the EJA policies, this contributes to form practices unlinked of the reality of the students researched. Also what was evidenced that the explosion of the number of students which some disability that were enrolled at this education modality, showing that the Young and Adults education has become a point of insertion to students who were excluded of the regular education.